Analysis of Journey to Work Travel Behavior by Car and Bus in the Sydney Metropolitan Region - Suthanaya P.A. (Civil Engineering Dimension, 2011)
Car dependence is a fundamental problem in the sustainability of cities with low-density suburban sprawl. Increasing the use of public transport is one of the policy objectives commonly adopted to overcome this problem. It is essential to study journey to work travel behavior by car and bus. This paper applied preference function to analyze travel behavior and Moran’s I spatial statistic to evaluate the spatial association. The results indicated that the commuting preferences of residents have moved towards distance maximization. In general, bus was preferred for shorter distance trips whilst car was preferred for longer distance trips. Unlike car, by increasing distances from the Central Business District, residents tended to use bus for shorter distance trip. A significant positive spatial association was identified for both the slope preferences by car and bus where zones with a preference towards longer or shorter trips tended to travel to zones with similar preferences.